IMPROVING STUDENTS VOCABULARY MASTERY AT TENTH GRADE OF SCIENCE 1 OF SMA AL-AZHAR 3 BANDAR LAMPUNG BY USING COMBINATION OF ANAGRAM AND KEYWORDS - Kinanti Rahmawati; Dameria Magdalena Sidabalok (Universitas Bandar Lampung, 2016)
Vocabulary is one of the important skills must be mastered to acquire the English. Therefore the purpose of this research is to observe the use of the combination of anagram and keywords in improving students vocabulary mastery at tenth grade of Science 1 of SMA Al-Azhar 3 Bandar Lampung. The researcher conducted the students at tenth grade of science 1 of SMA Al-Azhar 3 Bandar Lampung that consist of 43 students.The researcher used the qualitative and quantitative design. The researcher did the research in six meetings consisted of two meetings of the preliminary study, four meetings of the implementation of the combination of anagram and keywords. In the preliminary study, it was found that many students are poor of the English vocabulary. They were difficult to catch the teachers instruction when the teacher spoke in English. The researcher used the instruments; observation checklist, video recorder and students vocabulary test to gather the data. Then, in the final mean score got the result was 81.74 of 43 students. There were 84 % of 43 students who could pass the minimum score 80. So, based on the result, it explained after the implementation of the combination of anagram and keywords, the students got the good improvement in the vocabulary mastery.